Impact dynamics models: A short review on nonlinearities effects - Varanis, Marcus; Mereles, Arthur G.; Balthazar, Jose M. [UNESP]; Tusset, Angelo M.; De Oliveira, Clivaldo (Praise Worthy Prize, 2017)
Impact is a phenomenon present in a great number of situations, and in some of them, there is a need to know the properties of the impact on the bodies that collide. In that sense, this paper presents an impact model that represents a vehicle collision where the phenomenon is modeled as a spring-mass system. In order to establish a model that can properly represent the phenomenon, the spring and the damper of the system were considered to have linear and nonlinear characteristic, so that the system that best represents the phenomenon could be evaluated by comparing its responses with an experimental signal obtained in the literature. Also, the fractional theory was used in order to check its suitability to describe the phenomenon. The paper presents four cases: a linear system, a system with a spring with a cubic force-deflection behavior, a damper with a fractional damping order and a spring with elasto-plastic characteristic.
Keywords: Fractional damping; Impact model; Nonlinear model; Spring-mass system; Vehicle collision